Modeling Brand Trust through Social Proof Mechanisms in an Environment of Information Oversaturation - Ladyk, Kostandian (Актуальні питання економічних наук, 2025)
The purpose of the article is to analyze the main mechanisms of building trust in a brand in conditions of information overload and to develop an integrated model for overcoming consumer skepticism. The study is based on theoretical generalization and systematic analysis of the multi-component structure of trust, which covers cognitive, emotional, behavioral, as well as additional value, communicative, and social aspects. The analysis method was used to study the principles of Robert Cialdini’s social confirmation theory, which is the basis for effective marketing tools. Based on these data, a proprietary model was developed using the synthesis method, which reflects the relationship between the components of trust and the tools for its formation. The results show that in today’s unstable marketing environment, where consumers are faced with a huge flow of advertising messages every day, traditional promotion channels are losing their effectiveness. Instead, social confirmation mechanisms play a decisive role in this process. The study shows that tools such as influencer marketing, online reviews, ratings, as well as the psychological effect of “following the crowd” and storytelling are extremely powerful. They allow brands not only to overcome information overload, but also to form lasting relationships with consumers by influencing various aspects of trust. It is emphasized that these mechanisms are a strategic tool for building long-term loyalty. The conclusions indicate that the developed integrated model demonstrates how the harmonious combination of a multi-component trust structure with social confirmation mechanisms allows brands to build authentic and long-lasting relationships. The proposed model can serve as a practical tool for developing effective strategies focused on the quality of interaction with the audience. Further research may focus on a quantitative analysis of the model’s effectiveness and the study of the impact of new technologies on the formation of consumer trust.